Morphological and Genetic Variation of Filopaludina javanica (von dem Busch, 1844) (Gastropoda: Viviparidae) from Madura Island, Indonesia - Nugroho, Hafiidh Haqqu; Ambarwati, Reni; Isnaningsih, Nur Rohmatin; Rahayu, Dwi Anggorowati (Bogor Agricultural University, Indonesia, 2026)
Filopaludina javanica (von dem Busch, 1844) is a freshwater gastropod species in the Viviparidae family. Filopaludina javanica is widely distributed in freshwater waters in Java (including Madura), Sulawesi, Sumatra, Borneo, Papua, Thailand, and Vietnam. The morphological, morphometric, and molecular characterization studies of F. javanica based on the COI gene originating from Madura Island are still quite limited. Therefore, this study aims to determine the morphological variations, morphometry, and molecular characters of F. javanica in Bangkalan, Madura. The samples used are the Taxonomy Laboratory collection from Madura Island, followed by morphological observations, morphometry, and analysis of DNA: isolation, amplification, electrophoresis, and COI gene sequencing. Morphological and morphometric variations in F. javanica from Madura Island showed seven types of morphological variations. Principal Component Analysis (PCA) scatterplot results showed morphometric clustering of F. javanica based on morphological type. Identification of F. javanica using BLAST and comparison with the GenBank database revealed five nucleotide base variations, with an overall genetic distance of 0.031. Therefore, the phylogenetic tree shows that F. javanica from Madura Island belongs to the same clade as F. javanica from Sarawak, West Java, and North Kalimantan.